Cultural traits and productive transformation: Colombia in international perspective (2019)
Drawing from the consideration of cultural values as an explanatory factor of economic development, this article correlates the cultural traits reported by Hofstede’s Cultural Dimension model with the results in terms of industrialization for Colombia and selected cultural clusters. By contrasting industrialization-oriented policy choices with the evolution of export composition and industrial competitiveness indicators, we conclude that guided by a short-term, materialistic, nepotistic, and intolerant to uncertainty orientation, Colombian economic authorities and elites have helped in the prolongation of an underdeveloped industrial structure by favoring closed groups through extractive institutions, while Asia, instead of adopting ‘western values’, has drawn upon a long-term orientation to implement risky but sound, coordinated, and convergent social and economic policies in order to industrialize.